The impact of physical activity on body mass index, fat%, waist circumference, blood pressure and basal metabolic rate in young adults - Soe, May Khin Soe; Mohd Noor, Noriah; Htite, Lwin Mar; Mohamad, Ahmad Sykirin; Mohd Noor Zaidi, Muhammad Ridzuan (2013)
This study was undertaken to examine the effect of daily physical activity on other physiological parameters in young healthy adults and conducted at Basic Medical Sciences Department laboratory in Kulliyyah of Pharmacy, International Islamic University Malaysia. Ninety nine undergraduate first year pharmacy students aged 20 to 23 years old both male and female with no known diabetes and other illness were included in this cross sectional study. The level of physical activities was categorized into 5 groups and value was ranked from 1.2- 2 in accordance with intensity of activity they have exerted. Their heights, weight, body mass index (BMI), waist circumference and systolic and diastolic blood pressure (SBP & DBP) were recorded serially. Pearson Correlation was analysed to detect the relationship between physical activity and other parameters. Fifty nine were female and 40 were male. According to the finding, 21 (21.2%) subjects were ranked into 1.2 as they were sedentary life without doing any regular exercise; 39 (39.4%) were lightly active (ranked 1.375), 27 (27.3%) were moderately active (ranked 1.55) and 12 (12.1%) were very active (ranked 1.725). Thus, 60 (59.6%) were less active. The mean value of BMI, fat percentage, waist circumference, SBP& DBP and basal metabolic rate in female are 22.03 ± 4.02 kg/ M2 and 25.76 ± 4.82%, 69.07±7.46 cm, 105.35±12.76/66.5± 8.51mmHg and 1349.60 ±106.91 while these value in male are 23.36 ±4.16 kg/ M2; 16.58 ± 4.99%, 80.5450 ±9.92 cm, 119.32±14.77/ 68.51±10.33 and 1655.68 ±208.80 respectively physical activity was significantly correlated with BMI (r=.236*, P= .019), waist circumference (r=.431**, P= .000), waist hip ratio (r=.370**, P= .000), SBP (r=.255*, P= .011) and basal metabolic rate (r= .487**, p= .000) in these young adult group. Lack of physical activity may gain in BMI and increase energy storage lead to obesity towards the early onset of type 2 diabetes mellitus. Key words: Physical Activity, BMI, Fat Percentage, Waist Circumference, Basal Metabolic Rate